Effect of Feeding Fresh or Frozen Breast Milk on the Gut Microbiota of Premature Infants: A Prospective Observational Study - Merter, Ozlem Selime; Altay, Naime (Sage Publications Inc, 2024)
Background Breast milk is essential for premature infants. It contains a variety of functional and protective nutrients that help to create a suitable microenvironment for intestinal development and maturation. This prospective and observational study was planned to examine the effects of feeding premature infants with fresh or frozen breastmilk on their gut microbiota.Materials and Methods The study was carried out with a total of 40 infants, with a gestational age of 28-326 weeks, fed fresh (n = 20) or frozen (n = 20) breastmilk. Stool samples were stored at -80 & DEG;C until analysis. Infants were included in groups based on the feed type, which accounted for more than 70% of their 10-day feeding. The Mann-Whitney U, Chi-square, and t-tests were used to evaluate the demographic data. Stool samples were analyzed by sequencing the V3--V4 region of the 16S rRNA gene from the extracted DNA for microbiota analysis.Results Streptococcus and Enterobacteriales, the majority of which are considered human pathogens, in infants receiving frozen breastmilk (Streptococcus 69%, Enterobacteriales 79%) was higher than that in infants receiving fresh breastmilk (Streptococcus 16%, Enterobacteriales 49%). Further, the Lactobacillus and Bifidobacterium species were more abundant in infants who received fresh breastmilk (Lactobacillus 17%, Bifidobacterium 12%) than in infants who received frozen breastmilk (Lactobacillus 3%, Bifidobacterium 1%).Conclusion Thus, compared to frozen breast milk, fresh breastmilk has an effect on the diversity of preterm infants' gut microbiota.
Keywords: breastmilk; microbiota; nursing; premature infants; neonatal intensive care unit